2014
DOI: 10.1128/aac.01842-13
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei Isolates from Sarawak, Malaysian Borneo, Are Predominantly Susceptible to Aminoglycosides and Macrolides

Abstract: h Melioidosis is a potentially fatal disease caused by the saprophytic bacterium Burkholderia pseudomallei. Resistance to gentamicin is generally a hallmark of B. pseudomallei, and gentamicin is a selective agent in media used for diagnosis of melioidosis. In this study, we determined the prevalence and mechanism of gentamicin susceptibility found in B. pseudomallei isolates from Sarawak, Malaysian Borneo. We performed multilocus sequence typing and antibiotic susceptibility testing on 44 B. pseudomallei clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 32 publications
7
71
1
3
Order By: Relevance
“…This antibiotic is a known substrate of AmrAB-OprA (15,25,35). Curiously, in the closely related species Burkholderia thailandensis, overexpression of AmrAB-OprA can lead to DOX MICs up to 32 g/ml (36), which was not observed in this study.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…This antibiotic is a known substrate of AmrAB-OprA (15,25,35). Curiously, in the closely related species Burkholderia thailandensis, overexpression of AmrAB-OprA can lead to DOX MICs up to 32 g/ml (36), which was not observed in this study.…”
Section: Discussioncontrasting
confidence: 42%
“…Unlike the BPSL3085 knockouts, removal of amrR did not detectably alter the DOX MIC in either strain (Table 2). To determine the effect of the Ser174Pro protein change on AmrR activity and verify functional upregulation AmrAB-OprA, we measured the MIC of gentamicin, a known substrate for this efflux pump (15,25). For MSHR0293 ΔamrR, the gentamicin MIC increased 8-fold (from 96 to 768 g/ml).…”
mentioning
confidence: 99%
“…This failure is likely due to the deletions of nucleotides G760 and C761 in amrB, resulting in the nonfunctional efflux pump AmrAB-OprA and susceptibility of Bp1651 to GEN. A majority of clinical isolates of B. pseudomallei found in Sarawak, Malaysian Borneo, are also GEN susceptible (67). Some of this susceptibility is attributed to a nonsynonymous SNP, C1102G, within amrB (67). We previously showed that the GEN-susceptible phenotypes of GEN-susceptible Thai isolates were due to either deletion of the amrAB-oprA operon or regulatory mutations affecting its expression (42).…”
Section: Discussionmentioning
confidence: 99%
“…This failure is likely due to the deletions of nucleotides G760 and C761 in amrB, resulting in the nonfunctional efflux pump AmrAB-OprA and susceptibility of Bp1651 to GEN. A majority of clinical isolates of B. pseudomallei found in Sarawak, Malaysian Borneo, are also GEN susceptible (67). Some of this susceptibility is attributed to a nonsynonymous SNP, C1102G, within amrB (67).…”
Section: Discussionmentioning
confidence: 99%
“…0.5 to 2 g/ml) were isolated from both clinical and environmental samples and contained a point mutation in amrB that inactivated AmrAB-OprA. The reversion of this mutation via in vitro exposure of the susceptible strains to gentamicin and kanamycin (40 and 30 g/ml, respectively) was able to restore aminoglycoside and macrolide resistance (625), highlighting the clinical concerns on current gentamicin use (e.g., 4 g/ml) in medium to isolate B. pseudomallei (626). In B. thailandensis, multidrug-resistant mutants selected by doxycycline overproduced AmrAB-OprA and BpeEF-OprC.…”
Section: Burkholderia Sppmentioning
confidence: 99%